Hamil Diluar Nikah Sebagai Alasan Dispensasi Kawin Di Pengadilan Agama Koto Baru Solok (Studi Penetapan Perkara Nomor 119/PDT.P/2020/PA.KBR) - Rahmad, Abd.; Oktavia, Monica (Normative Jurnal Ilmiah Hukum, 2023)
According to Article 7 Paragraph (2) of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, it is stated that: "In the event of a deviation from the age provisions as intended in Paragraph (1), the parents of the man and /or the woman's parents can ask the Court for dispensation for very urgent reasons accompanied by sufficient supporting evidence. The formulation of the research problem is 1) How do judges consider pregnancy out of wedlock as a reason for marriage dispensation at the Koto Baru Solok Religious Court in the Determination of Case Number 119/Pdt.P/2020/PA.KBr? 2) What is the legal analysis of pregnancy out of wedlock as a reason for marriage dispensation at the Koto Baru Solok Religious Court in Case Determination Number 119/Pdt.P/2020/PA.KBr? The problem approach is normative juridical and the data type is secondary data. Data collection techniques were obtained through library research. Data processing was editing and coding. Qualitative data analysis. Research result; Firstly, the Judge's considerations are classified into two, namely legal considerations that when the Judge gives a decision it must be in accordance with the legal arguments and evidence submitted, namely the applicant is 8 months pregnant, the applicant is still at school and there is a rejection at the Office of Religious Affairs regarding marriage. . Considering social justice, marriage is considered an alternative solution. The legal analysis of pregnancy out of wedlock as a reason for marriage dispensation at the Koto Baru Solok Religious Court is that the court agrees more with Imam Hanafi's opinion, namely "Women who have become pregnant because of adultery do not get iddah and are even allowed to marry them, but they are not allowed to have sexual relations. until giving birth." Once the child is born, the child only has a lineage relationship with his mother and his mother's family in accordance with Article 100 of the Compilation of Islamic Law. The advice is that it is hoped that children, teenagers and parents will be more careful and supervise their relationships so that they do not fall into promiscuity and it is hoped that law enforcers will continue to produce good decisions and determinations.